2007
DOI: 10.7589/0090-3558-43.2.242
|View full text |Cite
|
Sign up to set email alerts
|

The Elimination of Raccoon Rabies From Wolfe Island, Ontario: Animal Density and Movements

Abstract: ABSTRACT:During 1996 to 1998, an average of 52% to 55% of the raccoon (Procyon lotor) population on Wolfe Island, Ontario was vaccinated against rabies during proactive trap-vaccinaterelease (TVR) operations. However, during 1999, the percent of the population vaccinated declined to 39% and an outbreak (6 cases) of raccoon rabies occurred on the island from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…However, results from other studies are contradictory because free-ranging skunks still demonstrate low population immunity in response to more commonly used ORV bait application densities (Table 1) [24, 50, 51, 68], which complicates management efforts because skunks are susceptible to spillover of raccoon rabies [11]. TVR is generally used to target animals in small areas (e.g., parks and urban neighborhoods) [69, 70, 66], but it is too labor intensive and expensive for broad-scale application [71]. This method is also used in contingency actions by the NRMP in response to ORV-zone breaches or threats of rabies spreading beyond existing zones [72].…”
Section: Rabies Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from other studies are contradictory because free-ranging skunks still demonstrate low population immunity in response to more commonly used ORV bait application densities (Table 1) [24, 50, 51, 68], which complicates management efforts because skunks are susceptible to spillover of raccoon rabies [11]. TVR is generally used to target animals in small areas (e.g., parks and urban neighborhoods) [69, 70, 66], but it is too labor intensive and expensive for broad-scale application [71]. This method is also used in contingency actions by the NRMP in response to ORV-zone breaches or threats of rabies spreading beyond existing zones [72].…”
Section: Rabies Management Strategiesmentioning
confidence: 99%
“…TVR was also used in an integrated point infection control (PIC) strategy in which raccoon rabies was detected across the St. Lawrence River in Ontario, Canada [71]. Rabies cases persisted until 2005, but Ontario is a much larger landscape to manage than New York, and the infection pressure from the US border states was constant [69, 71]. A TVR strategy was also used effectively in and around Flagstaff, Arizona following an outbreak of a bat rabies variant in striped skunks ( M .…”
Section: Rabies Management Strategiesmentioning
confidence: 99%
“…For example, Arjo et al (2008) reported adult and sub-adult male raccoon movements in Alabama of several kilometers (maximum >5.4 km) and adult females moving up to 3.5 km. However, farther movements (e.g., 24 km) have been reported for this species (Rosatte et al 2007). In this study, farther movements in continuous …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, previous studies have found larger home ranges of raccoons within a forested landscape when compared to suburban and rural landscapes (Prange et al 2004), and greater movement distances for male raccoons when compared to females (Rosatte et al 2007). Of interest, previous research has suggested that counties with a greater percentage of mixed forest habitat were less likely to experience large rabies epizootics than counties with a lower percentage of mixed forest habitat ( Jones et al 2003).…”
mentioning
confidence: 89%
“…However, a proportion of dogs are stray (i.e., free-roaming with or without owner, or feral, according to the OIE definition [6]), and owned dogs may also be aggressive and difficult to handle, therefore oral vaccination could be helpful [8]. Rabies has been successfully controlled in several European countries through oral vaccination of wildlife with vaccine baits and considerable success has been achieved in the control of Arctic fox rabies [9] and raccoon rabies in Canada and in the United States [10]. International guidelines for rabies control in dogs and implementation of field trials using oral vaccines are available [11,12].…”
Section: Introductionmentioning
confidence: 99%